Edukasi Pertolongan Pertama Pada Cidera Olahraga Melalui Metode Rice Di Sultan Camp Kota Gorontalo - Rifcha Paisal; Hartono Hadjarati; Meri Haryani; Safri Irawan; Khoirul Anwar Pulungan; Arief Ibnu Haryanto; Gina Riskita Datukramat; Haikal Malik; Rehan Antu; Moh. Rizki Paputungan (Universitas Negeri Gorontalo, 2026)
Sports injuries are a common problem in children's physical activities and can have more serious consequences if not handled properly. Lack of knowledge about first aid is a factor that can worsen injuries. This activity aimed to improve participants' knowledge and skills regarding first aid for sports injuries through the RICE (Rest, Ice, Compression, Elevation) method at Sultan Camp, Gorontalo City. The method used was health education with lectures, demonstrations, simulations, and hands-on practice for 30 elementary school students in grades III to VI. Evaluation was conducted using pretests and posttests to measure participants' knowledge levels before and after the activity. Results showed an increase in the average knowledge score from 58.3 in the pretest to 86.7 in the posttest. Furthermore, participants were able to effectively practice the steps of the RICE method during the simulation. This educational activity proved effective in improving participants' knowledge and skills regarding the initial management of sports injuries, thus supporting safety and health during sports activities.